CircRIC8B regulates the lipid metabolism of chronic lymphocytic leukemia through miR199b-5p/LPL axis - Zijuan Wu; Danling Gu; Ruixin Wang; Xiaoling Zuo; Huayuan Zhu; Luqiao Wang; Xueying Lu; Yi Xia; Shuchao Qin; Wei Zhang; Wei Xu; Lei Fan; et al. (Experimental Hematology & Oncology, 2022)
Abstract Objective Circular RNAs (circRNAs) play a critical role in the modulation of tumor metabolism. However, the expression patterns and metabolic function of circRNAs in chronic lymphocytic leukemia (CLL) remain largely unknown. This study aimed to elucidate the role of circRNAs in the lipid metabolism of CLL. Methods The expression and metabolic patterns of circRNAs in a cohort of 53 patients with CLL were investigated using whole transcriptome sequencing. Cell viability, liquid chromatography with tandem mass spectrometry (LC–MS/MS) analysis, lipid analysis, Nile red staining as well as triglyceride (TG) assay were used to evaluate the biological function of circRIC8B in CLL. The regulatory mechanisms of circRIC8B/miR-199b-5p/lipoprotein lipase (LPL) axis were explored by luciferase assay, RNA immunoprecipitation (RIP), qRT-PCR, and fluorescence in situ hybridization (FISH). CCK-8 and flow cytometry were used to verify the inhibition role of cholesterol absorption inhibitor, ezetimibe, in CLL cells. Results Increased circRIC8B expression was positively correlated with advanced progression and poor prognosis. Knockdown of circRIC8B significantly suppressed the proliferation and lipid accumulation of CLL cells. In contrast, the upregulation of circRIC8B exerted opposite effects. Mechanistically, circRIC8B acted as a sponge of miR-199b-5p and prevented it from decreasing the level of LPL mRNA, and this promotes lipid metabolism alteration and facilitates the progression of CLL. What’s more, ezetimibe suppressed the expression of LPL mRNA and inhibited the growth of CLL cells. Conclusions In this study, the expressional and metabolic patterns of circRNAs in CLL was illustrated for the 1st time. Our findings revealed that circRIC8B regulates the lipid metabolism abnormalities in and development of CLL through the miR-199b-5p/LPL axis. CircRIC8B may serve as a promising prognostic marker and therapeutic target, which enhances the sensitivity to ezetimibe in CLL.